Achiral polyamine-induced chiral zinc gallophosphates with fused double helix-like strands exhibiting blue to green photoluminescence. Issue 44 (25th October 2017) - Huang, Hui-Lin; Liu, You-Rong; Huang, Li-Hsun; Chiang, Ray-Kuang; Wang, Sue-Lein
Abstract : Chiral zinc gallophosphate structures with achiral linear-type polyamine templates exhibiting inorganic–organic double helix-like strands and intriguing blue to green photoluminescence. Abstract : This study found non-chiral polyamines to be effective in inducing chiral frameworks. Four zinc gallophosphates with a chiral UCSB-7 topology were generated from the use of four different linear-chain polyamines as templates. In the structure, helical inorganic strands and templates appeared to fuse into a double helix-like arrangement. Notably, they are the first chiral frameworks to display optical analogues and intriguing photoluminescence properties.